Synergistic study of a Danshen (Salvia Miltiorrhizae Radix et Rhizoma) and Sanqi (Notoginseng Radix et Rhizoma) combination on cell survival in EA.hy926 cells - Xian Zhou; Valentina Razmovski-Naumovski; Antony Kam; Dennis Chang; Chun Guang Li; Kelvin Chan; Alan Bensoussan (BMC, 2019)
Abstract Background This study investigated the protective effects of the Danshen (DS) and Sanqi (SQ) herb pair on cell survival in the human cardiovascular endothelial (EA.hy926) cell line exposed to injury. Methods Nine combination ratios of Danshen-Sanqi extracts (DS-SQ) were screened for their protective effects in the EA.hy926 cell line against two different cellular impairments induced by DL-homocysteine (Hcy) - adenosine (Ado) - tumour necrosis factors (TNF) and oxidative stress (H2O2), respectively. The type of interaction (synergistic, antagonistic, additive) between DS and SQ was analysed using a combination index (CI) model. The effects of key bioactive compounds from DS and SQ were tested using the same models. The compound from each herb that demonstrated the most potent activity in cell viability was combined to evaluate their synergistic/antagonistic interaction using CI. Results DS-SQ ratios of 6:4 (50-300 μg/mL) produced synergistic effects (CI < 1) in restoring cell viability, reducing lactate dehydrogenase (LDH) leakage and caspase-3 expressions against Hcy-Ado-TNF. Additionally, DS-SQ 6:4 (50-150 μg/mL) was found to synergistically protect endothelial cells from impaired cellular injury induced by oxidative damage (H2O2) by restoring reduced cell viability and inhibiting excessive expression of reactive oxygen species (ROS). In particular, the combination of salvianolic acid A (SA) and ginsenoside Rb1 (Rb1) at 4:6 (1-150 μM) showed synergistic effects in preventing cytotoxic effects caused by Hcy-Ado-TNF (CI < 1). This simplified combination also demonstrated synergistic effects on H2O2-induced oxidative damage on EA.hy926 cells. Conclusions This study provides scientific evidence to support the traditional use of the DS-SQ combination on protecting endothelial cells through their synergistic interactions.